Recurrent syncope in two patients with a sigmoid‐shaped interventricular septum and no left ventricular hypertrophy. Issue 6 (28th May 2015) - Yamaguchi, Yoshiaki; Mizumaki, Koichi; Iwamoto, Jotaro; Nishida, Kunihiro; Sakamoto, Tamotsu; Nakatani, Yosuke; Kataoka, Naoya; Inoue, Hiroshi
Abstract: Sigmoid‐shaped interventricular septum (SIS) is not uncommon in elderly patients and is considered a normal part of the aging process. However, several patients have been reported to have clinical symptoms due to the narrowing of the left ventricular outflow tract (LVOT). Two patients with SIS presented with recurrent episodes of syncope after drinking or taking sublingual nitroglycerin (NG). In both patients, a head‐up tilt test involving provocation with alcohol, NG, or isoproterenol induced the vasovagal reflex along with an increase in the pressure gradient between the apex and LVOT. The patients experienced no further episodes of syncope after initiating bisoprolol treatment. In patients with SIS, induction of the vasovagal reflex via an increase in left ventricular (LV) pressure due to LVOT obstruction concomitant with increased LV construction is a potentially important cause of syncope, which may be effectively prevented by beta‐blockers.